Reliability of self-employment intentions instrument among international students in Indonesian university - Subhan, Mhd; Zein, Mas’ud; ., Akhyar; Hakimie Zainal Abidin, Mohd; Ali, Sallehudin; Amat, Salleh; Izwan Mahmud, Mohd; Hanim A Hamid, Aida; Yazid Abu Bakar, Abu (International Journal of Engineering and Technology, 2018)
This paper examines the validation instrument used to measure the psychometric status of the self-employment intentions. Self-employment intentions are crucial to identify the university students in order to confirm their decision making. They are a questionnaire to measure graduation in university to start choice on their careers. This instrument is composed of 11 items and was carried out to 115 international students studying in one Indonesian higher education. There were 49 male and 66 female respondents involved in this study. The Cronbachâ€™s Alpha value was .94 which strongly suggest that the instrument has an excellent reliability. This study points out that self-employment intentions are suitable to be used by college personnel and counselors to examine and identify self-employment intentions among international students in Indonesian higher education. Implications for future study will also be discussed.Â